2022
DOI: 10.1111/tbed.14518
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter positivity and public health risks in live bird markets in Busia, Kenya: A value chain analysis

Abstract: Live bird markets (LBMs) provide integral hubs for 95% of poultry produced for food.Surveillance systems in LBMs serving smallholder farmers in sub-saharan Africa are often non-functional, and data about public health risks and emerging pathogens are lacking. Studies in Kenya have reported 29-44% Campylobacter prevalence in poultry. We analysed such LBMs in Kenya for likely transmission of Campylobacter from poultry to humans. We conducted a cross-sectional survey among 186 live poultry traders (LPTs) in 14 LB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
(118 reference statements)
0
1
0
Order By: Relevance
“…The relatively high Campylobacter prevalence in chicken of 44.4% found in this study is comparable to that reported by other studies carried out in Kenya. Poultry are documented asymptomatic reservoirs for thermophilic Campylobacter , with studies in Kenya reporting prevalence of 29–44% [ 9 , 41 ]. However, a number of studies in this country have reported prevalence values higher than 44% [ 8 , 10 , 12 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relatively high Campylobacter prevalence in chicken of 44.4% found in this study is comparable to that reported by other studies carried out in Kenya. Poultry are documented asymptomatic reservoirs for thermophilic Campylobacter , with studies in Kenya reporting prevalence of 29–44% [ 9 , 41 ]. However, a number of studies in this country have reported prevalence values higher than 44% [ 8 , 10 , 12 , 35 ].…”
Section: Discussionmentioning
confidence: 99%